Death Ritual Practices Among the Dangaura Tharu of Nepal - Chaudhary, Shiv Charan (Far Western Review, 2025)
This study examines the death ritual practices of the Dangaura Tharu community in Nepal, focusing on how these rituals embody cultural beliefs, social values, and community solidarity. It aims to explore the spiritual, social, and symbolic meanings of death rites such as body washing and wrapping, the use of khatiya (bamboo bed), lighting the diyo (lamp), offering rice, and performing purification rituals (kriya). Conducted in the Kailali and Bardiya districts through qualitative ethnographic methods, the research engaged 25 participants, including ritual specialists (guruwa, kesauka), elders, and bereaved families. Data were gathered through participant observation, interviews, and group discussions. The study draws on Durkheim’s theory of social cohesion, Blumer’s symbolic interactionism, and Goffman’s theory of ritual interaction to interpret how collective mourning and symbolic acts reaffirm unity, moral order, and social continuity. Findings reveal that each ritual act from carrying the body to observing food restrictions and performing kriya carries profound social and spiritual significance, reinforcing kinship, gender, and generational roles within the Tharu community. In spite of modern challenges such as migration and state health interventions, these rituals demonstrate the Tharu’s cultural determination and continuing respect for ancestors. The study is significant for understanding how traditional rituals mediate between individual emotion and collective identity, transforming grief into social renewal, and serves as a valuable foundation for future researchers interested in the connection of ritual, belief, and social cohesion in indigenous communities of Nepal.